An assistive technology package for students with attention deficit hyperactivity disorder - Beltran, Michelle Arlene C. (2009)
Limited literature on the effecfs of computer on the learning of students with ADHD established the need to evaluate a product, Tekkids, as an assistive technology for these students. The paper aimed to identify the effects of the use of Tekkids on students with ADHD using the Behavior Interaction Tool (BIT). A one-group pretest posttest design was used with 12 mainstream students with ADHD in grades 1 and 2. The BIT scores showed an improvement in student behavior after using the courseware. Attaching a computer speaker as an assistive technology during the implementation phase proved valuable in obtaining positive response. While students demonstrated positive behavior with adults and with the courseware, they had dificulty working with their peers, particularly their partner since they generally tried to monopolize computer use.